A survey on the knowledge and attitudes among the students of Al-Azhar University to HIV/AIDS, the Gaza Strip-Palestine - Basil Jabber Kanoa; Osama S AbuNada; Mazen A El-Sakka; Moain A Kariri; Adnan I Al-Hindi (Turkish Society of Public Health Specialists, 2015)
Objective: The study assessed the knowledge and attitudes of students' at a university in Gaza regarding HIV/AIDS and identified differences in knowledge about HIV, and attitudes by gender, locality, and social and economic status. Methods: This descriptive study targeted 492 students of Al-Azhar University-Gaza. The participants completed self-administered questionnaires that included the following dimensions: socio-demographic, measurements of student's knowledge level and measurement of student's attitudes towards HIV/AIDS. Results: Findings showed moderate level of knowledge regarding HIV/AIDS although there was a very low of perception regarding the acceptance and sharing of HIV/AIDS persons. It means that only one third of the study respondents are willingness to be in close touch with people living with HIV or even communication with them, and less than fifty percent thought that it is their right to be engaged in a public or governmental job, stigma and discriminatory attitudes toward HIV/AIDS persons is high only 48% of the students thought it right to employ people living with HIV (PLHIV) and 35.5% refused to work in the same place with PLHIV. Conclusion: This study indicates the need for improving the level of knowledge as well as promoting the students' towards positive attitude. Key words: AIDS, Knowledge, attitude, students, HIV, Gaza